2016
DOI: 10.1259/bjr.20150705
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for accurate CT diagnosis of suspected acute aortic syndrome (AAS)—on behalf of the British Society of Cardiovascular Imaging (BSCI)/British Society of Cardiovascular CT (BSCCT)

Abstract: Accurate and timely assessment of suspected acute aortic syndrome is crucial in this life-threatening condition. Imaging with CT plays a central role in the diagnosis to allow expedited management. Diagnosis can be made using locally available expertise with optimized scanning parameters, making full use of recent advances in CT technology. Each imaging centre must optimize their protocols to allow accurate diagnosis, to optimize radiation dose and in particular to reduce the risk of false-positive diagnosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…The following variables were electronically abstracted from structured databases drawn from the electronic health record: age, sex, ethnicity, height, weight, past medical history (hypertension, diabetes, aortic stenosis), predisposing syndromes associated with TAAD (Marfan's, Turner's, fibromuscular dysplasia) and family history of aortic dissection or aneurysm. CT images were obtained using either 16‐ or 64‐slice technology on a variety of platforms, most being performed without electrocardiogram synchronized image capture (cardiac‐gating), as is commonplace under emergent diagnostic circumstances . Digitized CT images (iSite PACS, Koninklijke Philips NV) from the initial diagnostic study were analyzed by two emergency physicians (DGM and JAD) to obtain manual measurements of the AscAo diameter using the precontrast series.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following variables were electronically abstracted from structured databases drawn from the electronic health record: age, sex, ethnicity, height, weight, past medical history (hypertension, diabetes, aortic stenosis), predisposing syndromes associated with TAAD (Marfan's, Turner's, fibromuscular dysplasia) and family history of aortic dissection or aneurysm. CT images were obtained using either 16‐ or 64‐slice technology on a variety of platforms, most being performed without electrocardiogram synchronized image capture (cardiac‐gating), as is commonplace under emergent diagnostic circumstances . Digitized CT images (iSite PACS, Koninklijke Philips NV) from the initial diagnostic study were analyzed by two emergency physicians (DGM and JAD) to obtain manual measurements of the AscAo diameter using the precontrast series.…”
Section: Methodsmentioning
confidence: 99%
“…A key limitation of our data is the variability in AscAo size that occurs throughout the cardiac cycle, given that cardiac‐gated CT image capture was rarely employed in this study, as is typical under emergent diagnostic circumstances . Studies have reported average changes in AscAo diameters of 2 mm or 3% between end‐diastole and end‐systole, and guidelines thus recommend the use of CT detector‐arrays with > 64 rows in conjunction with cardiac gating for imaging capture .…”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, details of further discussion on various protocols and advantages and disadvantages of each are beyond the scope of the current review and may be found elsewhere. 10…”
Section: Multidetector Computed Tomography Imaging Protocolmentioning
confidence: 99%
“…Its inability to image the entire length of the aorta reliably means that it does not have the diagnostic certainty to be a standalone test, especially when the clinical stakes are high and the consequence of missing the diagnosis is catastrophic. 11 The idea of using ultrasound as a gatekeeper to CT scan is plausible, although its cost-effectiveness is doubtful as patients will be subjected to multiple testing and the proportion of patients with non-conclusive ultrasound reports is not negligible. However, just because we should not use TTE in some clinical scenarios does not mean that we would not use it at all.…”
mentioning
confidence: 99%